Fatal injuries while under the influence of psychoactive drugs: a cross-sectional exploratory study in England - Dryden Ruth; Cobain Kathryn; Ghodse Hamid; Schifano Fabrizio; Oyefeso Adenekan; Corkery John (BMC, 2006)
Abstract Background Studies of drug-related mortality rarely describe fatal injuries due to psychoactive drug intoxication (FIUI). The main aim of this study was to determine the nature, extent and pattern of FIUI. Methods This observational study covered the period January 1999 to December 2001. Data were provided by members of a study panel of coroners in England using a standard protocol. Sources of data for this study included autopsy protocols, death certificates, hospital records, police reports, toxicology reports and inquest transcripts. Inclusion criteria for this were (i) the mention of one or more psychoactive substances as contributing to fatality; and (ii) the presence of a Controlled Drug at post mortem. Results A total of 3,803 drug-related deaths of persons aged 16-64 years were reported by the study panel during the three-year period. The study panel accounted for 86% of drug-related deaths in England in this period. There were 147 FIUI cases (119 males, 28 females), giving a proportionate mortality ratio of approximately 4%. The majority of FIUI cases (84%) were aged 16-44 years, with a median age at death of 33 years (Quartile deviation = 7). Fifty-six percent of FIUI occurred in urban areas of England. The population of the study jurisdictions aged 16-64 years contributed 49,545,766 person-years (py) to the study, giving an annual crude rate of 3/1,000,000 person-years (py). Rates for male and females were 4.9 and 1.1/1,000,000 py respectively, giving a male/female rate ratio of 4.5 (95%CI = 2.9-6.8). The rates of intentional and unintentional FIUI were 2 and 1/1,000,000 py respectively. The leading mechanism for intentional FIUI was suffocation while the predominant mechanisms in unintentional FIUI were road traffic accidents and falls. There is a significant difference in the pattern of drug-specific risk between FIUI and fatal poisoning. Risks of intentional FIUI are elevated among Black and Minority Ethnic groups. Conclusion There are differences in the nature, extent and pattern of intentional and unintentional FIUI that should necessitate targeted prevention strategies. Also, there is an opportunity for cross-discipline collaboration between injury prevention specialists and substance abuse/mental health specialists.